2008
DOI: 10.4310/cms.2008.v6.n3.a13
|View full text |Cite
|
Sign up to set email alerts
|

On the finite time blow-up of the Euler-Poisson equations in $\Bbb R^{2}$

Abstract: Abstract. We prove the finite time blow-up for C 1 solutions of the attractive Euler-Poisson equations in R n , n ≥ 1, with and without background state, for a large set of 'generic' initial data. We characterize this supercritical set by tracing the spectral dynamics of the deformation and vorticity tensors.Key words. Euler-Poisson equations, finite time blow-up AMS subject classifications. 35Q35, 35B30 The Euler-Poisson equationsWe are concerned with the pressureless Euler-Poisson equations in R n , n ≥ 1,Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…They identify if-and-only-if, pointwise conditions for global existence of C 1 solutions to restricted Euler-Poisson systems. Chae and Tadmor [10] further extend the Critical Threshold argument to multi-D full Euler-Poisson systems (1.2a), (1.2b) with attractive forcing k < 0. Their result, however, offers a blow-up region When tracking other results on the well-posedness of Euler-Poisson equations, we find them commonly relying on (the vast family of) energy methods and thus fundamentally differ from our pointwise results obtained via the Lagrangian approach.…”
Section: Corollary 12 Consider the N-dimensional Euler-poisson Systemmentioning
confidence: 96%
See 2 more Smart Citations
“…They identify if-and-only-if, pointwise conditions for global existence of C 1 solutions to restricted Euler-Poisson systems. Chae and Tadmor [10] further extend the Critical Threshold argument to multi-D full Euler-Poisson systems (1.2a), (1.2b) with attractive forcing k < 0. Their result, however, offers a blow-up region When tracking other results on the well-posedness of Euler-Poisson equations, we find them commonly relying on (the vast family of) energy methods and thus fundamentally differ from our pointwise results obtained via the Lagrangian approach.…”
Section: Corollary 12 Consider the N-dimensional Euler-poisson Systemmentioning
confidence: 96%
“…Both matrices are used to study the spectral dynamics of Euler systems (see e.g. [8] for M and [10] for S). The relation between the spectra of M and S is described in the following.…”
Section: Spectral Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The local existence for the systems can be found in [16,18,1,12]. The analysis of stabilities for the systems may be referred to [11,[19][20][21]9,10,23,3,7,25].…”
Section: Introductionmentioning
confidence: 99%
“…For the model without damping relaxation, global existence in the neighborhood of a steady state was obtained in [8]. On the other hand, finite time blowup results for attractive forces were obtained in [18], and for repulsive forces in [21,3,4]. Beyond the two scenarios of global existence of smooth solutions and finite-time breakdown, a third scenario of conditional regularity was promoted in [5,6,14,15], where it was shown that there exists a "large" set of O(1) initial configurations which lead to global smooth solutions, and the complementary "large" set of O(1) initial configurations which yield finite-time breakdown.…”
Section: Introductionmentioning
confidence: 99%